Qualitative and quantitative phenolic compounds analysis of dicranopteris linearis different fractional polarities leaves extract - Othman, Rashidi; Ramya, Razanah; Mohd Hassan, Norazian; Kammona, Suhair (SET PUBLISHER, 2020)
Dicranopteris linearis occupies in an open ground that contains poor soils and often colonizing disturbed space that partly shaded area. It has been known for various traditional values including medicinal, edible food, soil erosion protection, pen and furniture. Even though the plants possess both economic and medicinal value, they still form the neglected group of a plant. The present study was carried out to characterize the phenolic compounds in D. linearis leaves extract in different fractional polarities qualitative and quantitatively. Dried leaves of D. linearis were successfully extracted by using water extraction before separated by petroleum ether, ethyl acetate and butanol fractions. All the fractional extracts have been analysed by using GCTOF-MS and HPLC. The result from GCTOF-MS analysis of fractional extracts showed 38 compounds found in petroleum ether, ethyl acetate and butanol extracts. However, only four phenolic compounds were identified through HPLC analysis in ethyl acetate and butanol extracts which were 2-Methoxy-4-vinylphenol, Vanillin, 4-Hydroxybenzaldehyde and 4-Hydroxybenzohydrazide. The results revealed that D. linearis contained 699.83 ± 6.26 μg GAE /g DW of total phenolic acid whereas individual phenolic acids were predominantly caffeic acid (0.44 ± 0.01 μg/g DW) and ferulic acid (0.22 ± 0.00 μg/g DW) in ethyl acetate and caffeic acid (0.10 ± 0.00 μg/g DW) and 2-Coumaric acid (0.44 ± 0.00 μg/g DW) in butanol extracts. In the present study, the plant extracts demonstrated the highest phenolic compound detected in ethyl acetate and butanol compared to petroleum ether extract.